On a System of Nonlinear Variational Inclusions with Hh,η-Monotone Operators - Zeqing Liu; Jeong Sheok Ume; Shin Min Kang (Abstract and Applied Analysis)
This paper is concerned mainly with the existence and iterative approximation of solutions for a system of nonlinear variational inclusions involving the strongly Hh,η-monotone operators in Hilbert spaces. The results presented in this paper extend, improve, and unify many known results in the literature.